Kinerja Struktur Gedung Menggunakan Analisis Pushover Gedung Graha Pramesti - Roihan Aldiansyah (Jurnal Vokasi Teknik Sipil, 2025)
Many earthquakes have occurred in Indonesia and one of them is Malang City, which has various impacts including casualties and total building damage. The impact of earthquakes on social and economic aspects is very large. The purpose of this study is to determine the performance of the “Graha Pramesti” Training Center building against the threat of earthquakes. This research method uses pushover analysis. Pushover analysis is carried out to evaluate the critical points of the structure against earthquake loads with the concept of providing gradual loads until they match the displacement target. The analysis was carried out based on SNI 1726-2019 standards and ATC-40 performance criteria, with structural modeling using ETABS. The results of the research analysis are the capacity curve and the maximum value of the total drift direction X = 0.0079 and Y = 0.0069. The results of the building structure are at the Immediaty Occupancy (IO) performance level which indicates that the building remains safe, but there is still a risk of minor structural damage when an earthquake occurs. Thus, the building can be immediately reused without significant repairs. Keywords: Pushover Analysis, ATC-40, Building Structure Design, SNI 172-2019.